A comprehensive review on stability of therapeutic proteins treated by freeze-drying: induced stresses and stabilization mechanisms involved in processing. Issue 16 (12th December 2022) - Wang, Zhe; Li, Linlin; Ren, Guangyue; Duan, Xu; Guo, Jingfang; Liu, Wenchao; Ang, Yuan; Zhu, Lewen; Ren, Xing
Abstract: Therapeutic protein preparations are usually stored in a solid state to reduce the physical and chemical degradation by removing most of the solvent (mostly water) in liquid protein preparations, improving stability and maintaining biological activity. Freeze-drying (FD) is a common method to produce the dehydrated therapeutic protein. However, various induced stresses exist in the processing steps involved in FD, such as freezing process, primary drying, and secondary drying, may cause protein instability. To overcome this problem, two means are often employed: adding stabilizers to protect proteins from physical damage associated with the FD process; optimizing parameter conditions during the FD process to reduce protein degeneration. Therefore, a deep understanding of the protein preparation formula composition and FD process parameters is crucial for the development of stable therapeutic protein products. This study reviewed the stabilization mechanisms of protein during FD, focused on the factors that induce protein instability, and discussed the relationship between protein structure changes and instability, expected to provide references for solving the instability during protein freeze-drying and storage.